The impact of chronic in vivo glucocorticoid excess on the functional characteristics of human skin fibroblasts obtained from patients with endogenous Cushing's syndrome. - Zervolea, I; Pratsinis, H; Tsagarakis, S; Karavitaki, N; Stathakos, D; Thalassinos, N; Kletsas, D (2005)
OBJECTIVE: Chronic exposure to elevated glucocorticoid (GC) concentrations induces detrimental effects in several tissues. In the skin, GCs provoke intense alterations on various parameters of the physiology of fibroblasts, cumulatively leading to skin atrophy and impaired wound healing. As there are concerns that GCs may generate permanent adverse functional changes, we have investigated whether chronic in vivo exposure to GC excess results in persisting defects in skin fibroblasts. DESIGN AND METHODS: We have studied in vitro primary skin fibroblast cultures obtained from patients suffering from endogenous Cushing's syndrome (CF), as well as from sex- and age-matched normal donors (NF). The following functional parameters were investigated: cell proliferation, secretion of collagen, matrix metalloproteinases (MMPs) and their inhibitors (tissue inhibitors of metalloproteinases; TIMPs) and contractile capacity. RESULTS: CFs, grown under standard culture conditions in the absence of a hypercortisolemic milieu, exhibited an increased proliferative capacity and a higher final cell culture density compared with NFs. Collagen synthesis, in the absence or presence of transforming growth factor-beta, was equal to that of NFs. However, CFs secreted comparatively lower levels of MMP-1, MMP-2 and TIMP-1, and nearly equal levels of TIMP-2. CFs also exhibited an increased ability to contract gels of polymerized collagen. CONCLUSIONS: Collectively, these functional characteristics of CFs are in contrast to the known catabolic effects of GCs, and suggest that prior exposure to GC excess is not associated with a persisting adverse outcome in the functional phenotype of the fibroblasts.